ANALYSIS OF THE QUALITY OF CUSTOMER SATISFACTION IN WORKSHOP Nasmoco ringroad SOLO - ACHMAD AFRIADI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2019)
Satisfaction is feeling happy or disappointed someone who emerged after comparing the performance (or outcome) products that are considered on the performance (or outcome) is expected. If the performance fails to meet expectations, consumers will not be satisfied. Tujuan study was to determine the effect of service factors either partially or simultaneously covering; tangible, reliability, responsiveness, empathy and assurance of customer satisfaction in the garage Nasmoco Ringroad Surakarta.Survey research methods used in this study with the consumer population Nasmoco Ringroad Solo workshop. The sampling technique in the form of accidental sampling study of 100 samples of respondents through filling a questionnaire on differentiation, service and innovation on consumer purchasing decisions. While the data analysis to test the hypothesis used multiple linear regression, t test, F test, and the coefficient of determination R Square.The results showed that: 1) Physical evidence of an effect on customer satisfaction, 2)reliability influence on satisfaction customer. 3) responsiveness affect the customer satisfaction customer, 4)collateral effect on satisfaction customer, 5) empathy effect on satisfaction customer. Simultaneous test results indicate that the independent variable is the quality of service (physical evidence, reliability, responsiveness, assurance and empathy) effecting simultaneously on customer satisfaction, Customer satisfactionof 45.3% can be explained by physical evidence, reliability, responsiveness, assurance and empathy, while the remaining 54.7% is explained by factors - other factors beyond the studied,Â